Improving Students' Learning Discipline in Science Learning Through Students' Facilitation Method - Sari, Yuli Permata (Program Magister Teknologi Pendidikan Universitas Jambi, 2020)
The aim of the research is to determine the increase in student learning discipline in science learning through the habituation method in the VA class of elementary school 34/I Teratai. This type of research is classroom action research. The subjects and location of the research were students in the VA class of elementary school 34/I Teratai with a total of 21 students. In accordance with the achievement of the objectives of this research, it was carried out in 3 cycles. The data in the research was obtained from observations, documentation and tests. Data analysis was carried out descriptively. The results of this research show that in cycle I there were 10 students who completed with a percentage of 47.62%, those who did not complete were 11 students with a percentage of 52.38%, in cycle II there were 14 students who completed with a percentage of 66.67%, and those who did not complete were 7 students with a percentage of 33.33 %. In cycle III, 17 students completed it with a percentage of 80.95%, 4 students did not complete it with a percentage of 19.05%. Based on the research results obtained, it can be concluded that there was an increase in student learning discipline activities, which in cycle I achieved completeness by 47.62%, in cycle II achieved completeness by 66.67% and in cycle III achieved completeness by 80.95%.